1996
DOI: 10.1152/ajpcell.1996.270.5.c1544
|View full text |Cite
|
Sign up to set email alerts
|

Delta F508-CFTR channels: kinetics, activation by forskolin, and potentiation by xanthines

Abstract: Trafficking, activation, and kinetics of delta F508-cystic fibrosis transmembrane conductance regulator (CFTR) and CFTR were compared in stably transduced C127I mouse mammary epithelial cells. Western blots detected a small amount of fully glycosylated delta F508-CFTR Efflux of 125I was stimulated by forskolin with the same mean effective concentration (EC50; approximately 0.5 microM) for CFTR and delta F508-CFTR cells, but the maximum response was reduced more than fivefold and its latency increased approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
109
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 25 publications
11
109
0
Order By: Relevance
“…The ⌬F508-CFTR channels exhibit several physiological abnormalities; one of them is the low P o observed in intact cells due to a reduced opening rate (20,22). It was suggested that this low opening rate was due to a very slow phosphorylation rate (30) and not to an intrinsic defect in the gating mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The ⌬F508-CFTR channels exhibit several physiological abnormalities; one of them is the low P o observed in intact cells due to a reduced opening rate (20,22). It was suggested that this low opening rate was due to a very slow phosphorylation rate (30) and not to an intrinsic defect in the gating mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of temperature (10) and addition of chemical chaperones such as glycerol (11) and trimethylamine-N-oxide (12) overcame impediments in the folding pathway of ∆F508 CFTR and allowed proper targeting, demonstrating that the mutant protein is still capable of assuming a mature conformation. However, at the cell surface the chloride channel revealed a decreased half-life (13,14) and reduced open probability and sensitivity to stimulation with cAMP agonists (10,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that the ER retention of ⌬F508-CFTR is not complete, and some ⌬F508-CFTR is constitutively expressed in the plasma membrane of primary epithelial cells from individuals homozygous for the ⌬F508 mutation (7)(8)(9)(10). Because ⌬F508-CFTR retains some Cl Ϫ channel activity when expressed in the plasma membrane (5,6,(11)(12)(13)(14), it would be desirable to increase the expression of ⌬F508-CFTR in the plasma membrane to alleviate the symptoms in CF patients. The trafficking of ⌬F508-CFTR to the plasma membrane can be increased by chemical means or reduced temperature (15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%